The influence of partial weight bearing on plantar peak forces using three different types of postoperative shoes. Issue 8 (December 2022) - Eidmann, Annette; Vinke, Wiebke; Jakuscheit, Axel; Rudert, Maximilian; Stratos, Ioannis
Abstract: Background: Therapeutic shoes and partial weight bearing regimes are used after foot surgery to prevent the operated region from excessive load. It remains unclear to which extent partial weight bearing reduces the plantar peak forces. Therefore, we investigated the correlation of weight bearing and plantar peak forces in commonly used therapeutic shoes. Methods: Three different weight bearing regimes (20 kg, 40 kg, full weight) were investigated in 20 healthy volunteers. Sensor insoles were used to measure peak forces of the forefoot, midfoot, heel and the complete foot using four kind of shoes (bandage shoe, forefoot relief shoe, short walker and standard sneaker). Peak forces were compared between shoes using one-way ANOVA. The influence of partial weight bearing relative to the peak forces was examined by linear regression analysis. Results: All therapeutic shoes reduced significantly peak forces of the fore- and midfoot when compared to the reference shoe; the largest reduction was achieved by the forefoot relief shoe (−70 % at forefoot). Weight load and the resulting peak force showed a positive linear correlation for all regions and shoe types. Partial weight bearing significantly reduced the forefoot's force ratio compared to full weight bearing for all shoes except the forefoot relief shoe. Conclusions: Partial weight bearing is a strong instrument to reduce plantar peak forces of the forefoot, additionally to the proven offloading effect of therapeutic shoes.